Penguatan Karakter Kewarganegaraan melalui Permainan Tradisional pada Anak di Komunitas Kampoeng Dolanan Surabaya - Andriani, Devi; Purba, Iman Pasu Marganda Hadiarto (Universitas Negeri Surabaya (Unesa), 2024)
Issues regarding character are basically issues of the future, the younger generation, and the civilization of a nation. Therefore, it is necessary to strengthen character from an early age in order to form and produce superior character and noble character, remembering that children are the next generation of the nation and as good citizens they must have civic character. Kampoeng Dolanan is a social community that focuses on preserving traditional games. The character strengthening theory used is Albert Bandura's observational learning theory which consists of four stages, namely attention, retention, reproduction and motivation. This type of research is qualitative research with a case study approach. Research data collection techniques include observation, semi-structured interviews, and documentation. The results of this research show that strengthening the character of children is very important because currently many young people play with gadgets excessively even without parental supervision, have broken homes, promiscuity, and so on. Moreover, strengthening children's character through play activities is something that is very popular so that children can do it with enthusiasm and bring joy. Apart from that, traditional games also have various positive values ??in them such as cooperation, honesty, courage, solidarity, and so on. The strategies used by Kampoeng Dolanan in strengthening civic character in children include play activities carried out regularly on school holidays, social differentiation in group formation, competition while playing, providing motivation and reflection at the end of play activity sessions. The types of traditional games used to strengthen civic character are tug of war, gobak sodor and bakiak because they are most often played in the Kampoeng Dolanan community.